Delaware journal of public health - Delaware Academy of Medicine; Delaware Public Health Association (Delaware Academy of Medicine, 2015)
The journal is Delaware-focused, but frequently includes articles, editorials, and research from national sources.
Keywords: Public health : Delaware : Periodicals; Public health : Periodicals; Public health; Public Health; Santé publique : Delaware : Périodiques; Santé publique : Périodiques; Santé publique; public health; Delaware; Delaware